Problematika Pembelajaran Maharatul Kalam Dalam Bahasa Arab (Studi Kasus Pondok Pesantren Al-Minhaj Shahabah, Bogor, Jawa Barat) - Alya Maulia Yusuf; Taufik Hidayat; Soraiya Usman (Journal on Education, 2024)
This study aims to analyze the problems in learning maharatul kalam (speaking skills) in Arabic at Pondok Pesantren Al-Minhaj Shahabah, Bogor, West Java. The research employs a qualitative method with a case study approach. Data were collected through observations, interviews, and documentation studies. The results show that students face both linguistic and non-linguistic challenges in their learning process. Linguistic challenges include difficulties in pronunciation, limited vocabulary, and complex grammatical understanding. Meanwhile, non-linguistic challenges encompass lack of confidence, fear of making mistakes, and fluctuating motivation. An analysis of student report cards indicates a fairly good level of effectiveness, but there is still room for improvement. Psychological factors and a learning environment that is not fully supportive also hinder the optimization of learning effectiveness. This research highlights the importance of a holistic and student-focused approach in teaching maharatul kalam to significantly enhance Arabic speaking skills.